Secure Key Distribution Using Quantum Cryptography (Global Journal of Computer Science and Technology, 2012)
Cryptography plays a vital role in Internet based applications. Present cryptographic systems on classical computers are providing sufficient security by utilizing symmetric and asymmetric cryptographic technologies but the advent invention of quantum computer makes the present asymmetric cryptographic systems vulnerable. The Quantum theory, which makes present cryptographic systems vulnerable, provides an alternative approach for secure key distribution. This paper depicts various issue related to conventional as well as quantum cryptography and secure key distribution using quantum cryptography.
Keywords: cryptography; symmetric; asymmetric; security; key; quantum; photons